2016
DOI: 10.1111/clr.12876
|View full text |Cite
|
Sign up to set email alerts
|

Experimental conical‐head abutment screws on the microbial leakage through the implant‐abutment interface: an in vitro analysis using target‐specific DNA probes

Abstract: Differences in the geometry of implant connections and abutment screws have impacted the microbial leakage through the implant-abutment interface. Implants attached with experimental conical-head abutment screws showed lower counts of microorganisms when compared with conventional flat-head screws.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
0
7
0
5
Order By: Relevance
“…Moreover, during mechanical loads, model B acts as a single body, reducing possible tilting forces that could create a gap between the structures of the connection, which is why it differs from the taper-locking model A. According to the literature, a conical-head internal screw prevents microbial leakage through the implant–abutment interface, ensuring a better seal [41]. One of the limitations of this study is that we focused exclusively on implant connections and, for this reason, the threaded parts of the system were neglected.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, during mechanical loads, model B acts as a single body, reducing possible tilting forces that could create a gap between the structures of the connection, which is why it differs from the taper-locking model A. According to the literature, a conical-head internal screw prevents microbial leakage through the implant–abutment interface, ensuring a better seal [41]. One of the limitations of this study is that we focused exclusively on implant connections and, for this reason, the threaded parts of the system were neglected.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are no data that could show that the presence of these microorganisms in the inner part of the dental implants could increase or even cause peri-implant infection. Recent in vitro data [60][61][62][63][64] have shown that Morse taper connections improve the mechanical sealing on the implant-abutment junction, but none of the aforementioned studies depicted a sealed chamber in any connection (external, internal, or Morse taper).…”
Section: Discussionmentioning
confidence: 99%
“…Microgaps between implant and abutment can harbor bacterial species and allow the bi‐directional leakage of microorganisms, fluids, and toxins through the interface. This process can lead to inflammatory responses in the peri‐implant soft tissues, bone resorption and, ultimately, implant failure 10 …”
Section: Introductionmentioning
confidence: 99%